A critical success model for PPP public housing delivery in Ghana. Issue 1 (1st February 2016) - Kwofie, Titus Ebenezer; Afram, Samuel; Botchway, Edward
Abstract : Purpose: – The nature and characteristics of critical success factors (CSFs) that influence success on public private partnership (PPP) arrangements on different project typologies vary between countries and regions. Studies confirm the lack of success on PPP approach on public housing project (PHP). The main challenge to PPP-PHP success has been identifying, analysing, categorizing and matching CSFs that are likely to influence the PPP-PHP outcome. The purpose of this paper is to identify the CSFs that influence PPP-PHP delivery in Ghana. This is premised on the theoretical implications that understanding the factors that influence the success on PPP-PHP projects is critical. Design/methodology/approach: – By adopting a 16 CSFs from literature and using a questionnaire survey, the factors that are critical to success on PPP-PHP approach in Ghana were identified. The questionnaires were administered on participants that have been involved in PPP-PHPs in Ghana. Findings: – The results revealed six CSFs that are critical towards success on PPP-PHPs in Ghana. The results also do not show significant variability in the agreement by the public and private stakeholder. Practical/implications: – The findings present useful lessons for parties in PPP-PHPs in Ghana to focus their attention to engender the needed atmosphere towards successful delivery in Ghana in the formulation of policies, decision frameworks and delivery strategies. Originality/value: – The study presents a critical success model that is applicable to PPP-PHP delivery in Ghana and potentially to other developing countries with similar socio-economic, political and organizational characteristics especially in Sub-Saharan Africa. It also affirms the fact that CSFs are contextual to project typologies and that different project types will reveal CSFs with varying significance in ranking. The findings should help in the development of efficient frameworks and policies for successes on PPP-PHPs in Ghana.